A system for predicting burning weather in the south-western Cape mountain catchment areas - Juhnke, Sieghard Rüdiger (Department of Environmental and Geographical Science, 2023)
This study addresses the problem of predicting suitable burning weather for the south-western Cape Province by means of synoptic analysis. Weather which is suitable for veld burning is defined in terms of maximum hourly windspeed (< 16 km/hr), maximum daily temperature (18° - 28°C) and minimum daily humidity (15 - 45%). Synoptic conditions which are associated with favourable burning weather are outlined. Burning weather in the study area was found to be associated with weak anticyclonic air flow. The pressure configuration which gives rise to the required anticyclonic flow consists of a high pressure cell over the eastern part of the subcontinent, a trough of low pressure along the north-western interior and the location of the climatological high pressure system of the South Atlantic Ocean to the south-west of the subcontinent. A model five-day sequence of pressure charts was developed for use as an analogue consultation system for predicting burning weather. During a test application of the model five-day sequence it could be shown that the system is useful for alerting catchment managers three days in advance, when to expect weather suitable for controlled burning.